Water bath sonicator integrated with PID-based temperature controller for flavonoid extraction - Zainul Abidin; M. Aziz Muslim; Muhammad Muqorrobin; Warsito Warsito (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
In this research, water bath sonicator was fabricated to extract bioactive compound of plants material using sound energy (ultrasonic waves) and heater. The bioactive compound, flavonoid, has high sensitivity to temperature and extraction time and previous research stated best treatment with combination of 45˚C and 20 minutes. Therefore, fabricated water bath sonicator was equipped with proportional integral derivative (PID) based temperature controller and timer. Based on a calculation using the Ziegler-Nichols tuning method, Kp, Ki, Kd parameters are 16.59, 0.0279, and 2463.6, respectively. The experimental result shows that the PID controller can perform as design specification with overshoot 1.39%, error steady-state 0.688% and settling time 37.2 minutes. Furthermore, it was proven that the PID controller has contribution to extract more flavonoid.